Proyecto de elaboración y aplicación de antígeno parasitario (strongyloides) en ovinos. - Salguero Guanoluisa, Diego Fernando (2022)
The present investigation was carried out to elaborate and apply a Strongyloides antigen, for which the presence of the Strongyloides parasite was determined in ovine animals of the Quinticusig parish, Sigchos canton, province of Cotopaxi, and to classify them according to their sex and age; The coproparasitary examination was carried out by sedimentation technique, where fecal samples were collected from 30 sheep, obtaining 100% of animals positive for Strongyloides, and grouping them into two groups according to sex, where 53% males and 47% females of the total population were obtained; the ages of the sheep ranged from 0-12 months 60%, animals older than 1 year up to 2 years 36. 67% and 3 years and older, 3.33%. It was determined that sex and age were not influential factors in the presence of Strongyloides. The immunological levels of Immunoglobulin E (IgE) and hematological values of the parasitized sheep were also measured by taking blood samples and sending them to laboratories, where it was found that 17% of the sheep population presented elevated IgE, while the evaluation of the results of hematological examinations at the global level within the sheep population were: leukocytosis (46. 67%), lymphocytosis (56.67%), microcytosis (60%), thrombocytosis (3.33%), thrombocytopenia (26.67%), hypochromia (3.33%) and anemia (13.33%). A Strongyloides parasitic vaccine was developed and applied to the sheep in the study, where 1.33% protein was obtained by bromatological examination. This research benefited local sheep producers in the area, as well as meat consumers and the human and animal population living with these parasitized animals. It generated an impact against problems of anthelmintic resistance caused by indiscriminate use of dewormers, and provided an alternative solution to the use of dewormers.